Identification of transcription factors involved in Candida albicans mistranslation - Oliveira, João Pedro Ferreira (2021)
Candida albicans is the main human fungal pathogen. It is usually commensal yet when immunocompromised individuals are exposed to it infections normally develop from mild rashes to systemic disease. Candida albicans is characterized by the reassignment of the CUG codon from Leucine to Serine by a hybrid serine tRNA (tRNACAGSer) which decodes the leucine-CUG as leucine (3 to 5 %) and as serine (95 to 97 %) under normal growth conditions. The tRNACAGSer is aminoacylated by two aminoacyl tRNA synthetases, the leucyl-tRNA synthetase (LeuRS) and the seryl-tRNA synthetase (SerRS). Previous studies showed that when Candida albicans is exposed to stress, namely temperature, pH, osmolarity and antifungals, the level of leucine misincorporation rises, suggesting that C. albicans regulates mistranslation levels in response to stress. In this thesis we started characterizing the mechanisms that controls Leu misincorporation in C. albicans. For this, C. albicans strains harboring deletions in genes of selected kinases and transcription factors were transformed with fluorescent reporter systems to monitor the levels of leucine and serine incorporation at CUG codons. The activity of the LeuRS (CDC60) and SerRS (SES1) promoter was quantified in several different physiological conditions using a second fluorescent reporter system. The results suggested that Leu misincorporation at CUG codons could be due to increased LeuRS expression or decreased SerRS expression. In the second part of this study, protein from C. albicans KO strain collection was extracted and the levels of LeuRS and SerRS were quantified by western blot using antibodies against both enzymes. LeuRS/SerRS expression ratio in the mutant relative to WT strains allowed the identification of 3 putative transcription factors that regulate the expression of LeuRS and SerRS, namely EFG1, MRR1 and ACE2